Autologous stem cell transplantation improves microcirculation in systemic sclerosis. Issue 1 (28th February 2008) - Miniati, I; Guiducci, S; Conforti, M L; Rogai, V; Fiori, G; Cinelli, M; Saccardi, R; Guidi, S; Bosi, A; Tyndall, A; Matucci-Cerinic, M
Abstract : Background: In systemic sclerosis (SSc) reduced capillary density decreases blood flow and leads to tissue ischaemia and fingertip ulcers. Nail fold videocapillaroscopy (NVC) is a diagnostic and follow-up parameter useful to evaluate the severity, activity and the stage of SSc microvascular damage. Autologous haemopoietic stem cell transplantation (HSCT) is a new treatment for patients with severe diffuse cutaneous systemic sclerosis (dcSSc) refractory to conventional therapies. We aimed to evaluate the improvement of microvasculature after HSCT using NVC. Methods: A total of 16 patients with severe dcSSc with a "late" videocapillaroscopy pattern underwent an immunesuppressive treatment: 6 were treated with HSCT and 10 with monthly pulse cyclophosphamide (CYC) 1 g for 6 months and then orally with 50 mg/day for further 6 months. NVC was performed before and after 3 months from the beginning of each treatment and then repeated every 3 months. Results: In all patients, before HSCT NVC showed large avascular areas and ramified capillaries and vascular architectural disorganisation ("late" pattern). At 3 months after HSCT, the NVC pattern changed from "late" into "active", showing frequent giant capillaries (>6/mm) and haemorrhages, absence of avascular areas and angiogenesis phenomena; 1 year after HSCT, microvascular abnormalities were still in the "active" pattern. In patients treated with CYC, no NVC modifications were observed during 24 months of follow-up and the pattern always remained "late". Conclusions: These results indicate that HSCT with a high dose CYC regimen may foster vascular remodelling, while CYC at lower doses and with a chronic regimen does not influence the microvasculature.